1992
DOI: 10.1002/ijc.2910510207
|View full text |Cite
|
Sign up to set email alerts
|

Laminin expression by two clones isolated from the colon carcinoma cell line lovo that differ in metastatic potential and basement‐membrane organization

Abstract: In the present report we describe the characteristics of 2 clones, E2 and C5, isolated from the human colon adenocarcinoma cell line LoVo. When grafted to immunosuppressed newborn rats, these clones formed tumors that varied with regard to differentiation rate, basement-membrane organization and lung metastatic potential. Production and distribution of laminin by E2, C5 and related tumors was studied by immunohistochemistry with an anti-laminin monoclonal antibody 4C12 (MAb 4C12). In lowly metastatic E2-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
(15 reference statements)
2
14
0
1
Order By: Relevance
“…E2 and C5 clones were originally reported to induce colon carcinoma xenografts that differed in basement membrane organization, cellular differentiation grade, and metastatic ability, C5 cells being significantly more prone than E2 cells to induce spontaneous lung metastases in immune-deficient hosts (Remy et al, 1992). We here identified the CD63 tetraspanin, not previously known to be implicated in colon cancer progression, and the ␣3 integrin chain as two components whose expression could modulate metastatic ability.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…E2 and C5 clones were originally reported to induce colon carcinoma xenografts that differed in basement membrane organization, cellular differentiation grade, and metastatic ability, C5 cells being significantly more prone than E2 cells to induce spontaneous lung metastases in immune-deficient hosts (Remy et al, 1992). We here identified the CD63 tetraspanin, not previously known to be implicated in colon cancer progression, and the ␣3 integrin chain as two components whose expression could modulate metastatic ability.…”
Section: Discussionmentioning
confidence: 74%
“…When grafted to immunosuppressed newborn rats, E2 and C5 cells induce tumors that differ in basement membrane organization, grade of tumor cell differentiation, and potential to spontaneously metastasize to the lungs of recipient hosts (Remy et al, 1992). The cDNA clones were from a normalized infant brain library and the arrays used in the present study consisted of PCR products from 2208 cDNA clone inserts subjected to clone and sequence-clustering analyses .…”
mentioning
confidence: 99%
“…In this study, we found that the ␤4 integrin subunit can enhance the migratory and invasive properties of the LoVo C5 clone that we isolated and characterized (Rémy et al, 1992). We propose that a mechanism contributing to this enhancement is the induction of MMP-2 expression.…”
mentioning
confidence: 72%
“…The role of the ␤4 integrin subunit in migration and invasion was tested by measuring the ability of LoVo C5 cells to metastasize in an experimental metastasis model (Rémy et al, 1992). Lung metastases developed in 43% of rats co-injected with LoVo C5 cells and the anti-␤4 antibody compared with only 8% in those injected with LoVo C5 cells only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation